2008
DOI: 10.1161/hypertensionaha.107.098855
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Mononuclear Cells Plays a Dominant Role in Their Adhesion to Mouse Femoral Artery After Injury

Abstract: Abstract-Leukocyte recruitment plays a pivotal role during inflammation after vascular injury. The importance of oxidative stress in vascular injury and its modulation by angiotensin II receptor blockers (olmesartan) have been demonstrated. We examined the contribution of leukocyte-associated oxidative stress in acute-phase leukocyte recruitment and its modulation by olmesartan. Male mice were treated with olmesartan (5 mg/kg per day) or vehicle for 7 days before the transluminal wire injury of the femoral art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 33 publications
(22 reference statements)
1
19
0
Order By: Relevance
“…We recently developed a novel intravital microscopic system to directly monitor leukocyte recruitment in athero-prone arteries in vivo. 17,18 Using our technique, we have found that oxidative stress has an important role in leukocyte recruitment after luminal injury and documented the anti-inflammatory potential of compounds related to cardiovascular diseases. 18 In the present study, we examined the effects of atorvastatin and amlodipine on the recruitment of leukocytes to the site of vascular injury.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…We recently developed a novel intravital microscopic system to directly monitor leukocyte recruitment in athero-prone arteries in vivo. 17,18 Using our technique, we have found that oxidative stress has an important role in leukocyte recruitment after luminal injury and documented the anti-inflammatory potential of compounds related to cardiovascular diseases. 18 In the present study, we examined the effects of atorvastatin and amlodipine on the recruitment of leukocytes to the site of vascular injury.…”
Section: Discussionmentioning
confidence: 93%
“…C-SF-1515, Cook, Bloomington, IN, USA), as previously described. 17,18 Briefly, the femoral artery was exposed, and upstream and downstream areas of the arterial branch were clamped. Then, a guide wire was inserted into the femoral artery and removed from the vessel, followed by branch ligation.…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations